Marriage markets how inequality is remaking the American family - Carbone, June 1953-; Cahn, Naomi R. (Oxford Univ. Press, 2014)
"There was a time when the phrase "American family" conjured up a single, specific image: a breadwinner dad, a homemaker mom, and their 2.5 kids living comfortable lives in a middle-class suburb. Today, that image has been shattered, due in part to skyrocketing divorce rates, single parenthood, and increased out-of-wedlock births. But whether it is conservatives bewailing the wages of moral decline and women's liberation, or progressives celebrating the result of women's greater freedom and changing sexual mores, most Americans fail to identify the root factor driving the changes: economic inequality that is remaking the American family along class lines. In Marriage Markets, June Carbone and Naomi Cahn, co-authors of the acclaimed Red Families v. Blue Families, examine how macroeconomic forces are transforming our most intimate and important spheres, and how working class and lower income families have paid the highest price. Just like health, education, and seemingly every other advantage in life, a stable two-parent home has become a luxury that only the well-off can afford. The best educated and most prosperous have the most stable families, while working class families have seen the greatest increase in relationship instability. Why is this so? This book offers a new answer: it is due to the economics of marriage markets, and of how men and women match up when they search for a life partner. For instance, when eligible (i.e., desirable and marriageable) men outnumber eligible women, the marriage and marital stability rates are significantly higher than when the reverse situation occurs - the exact situation we have in America today. The failure to see marriage as a market affected by supply and demand has obscured any meaningful analysis of the way that societal changes influence culture.